2019
DOI: 10.1093/beheco/arz100
|View full text |Cite
|
Sign up to set email alerts
|

Parental care buffers against effects of ambient temperature on offspring performance in an insect

Abstract: Understanding how animals respond to and cope with variation in ambient temperature is an important priority. The reason for this is that ambient temperature is a key component of the physical environment that influences offspring performance in a wide range of ectotherms and endotherms. Here, we investigate whether posthatching parental care provides a behavioral mechanism for buffering against the effects of ambient temperature on offspring in the burying beetle Nicrophorus vespilloides. We used a 3 × 2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Note that fewer larvae per brood survived in the 5 g switch experiment compared with the control experiment (Figure ). Many factors are known to influence offspring fitness, from biotic ones like competition with mites (Gasperin, Duarte, & Kilner, ) or quantity and quality of the food (Hopwood, Moore, & Royle, ; Rebar, Leggett, Aspinall, Duarte, & Kilner, ; Rozen, Engelmoer, & Smiseth, ) or abiotic ones like temperature (Grew, Ratz, Richardson, & Smiseth, ). However, since we kept environmental factors, such as temperature, light condition, soil properties, and food resources constant among the treatments, we presently have no explanation for the discrepancy in larval fitness between the control and the 5 g switch experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that fewer larvae per brood survived in the 5 g switch experiment compared with the control experiment (Figure ). Many factors are known to influence offspring fitness, from biotic ones like competition with mites (Gasperin, Duarte, & Kilner, ) or quantity and quality of the food (Hopwood, Moore, & Royle, ; Rebar, Leggett, Aspinall, Duarte, & Kilner, ; Rozen, Engelmoer, & Smiseth, ) or abiotic ones like temperature (Grew, Ratz, Richardson, & Smiseth, ). However, since we kept environmental factors, such as temperature, light condition, soil properties, and food resources constant among the treatments, we presently have no explanation for the discrepancy in larval fitness between the control and the 5 g switch experiment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reason for this small effect might be that males continue to feed from the carrion resource in the posthatching phase, that is, after the switch. A recent study has also shown that uniparental female care is more efficient under lower ambient temperatures compared with standard laboratory conditions (Grew et al, ). It might very well be possible that also the effects of a second caring parent might become more evident when environmental conditions are less favorable for the developing larvae.…”
Section: Discussionmentioning
confidence: 99%
“…It might, therefore, be possible that the beetles require a specific temperature for optimal development. In fact, a recent study found evidence that temperature has an effect on offspring number and fitness in N. vespilloides ( Grew et al 2019 ). Although soil temperature might influence pheromone transmission, it more probably has an effect on the prevailing number or activity of beetles and, therefore, males choosing to call on sites with warmer soil can attract more females.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the success of this species might lie in its elaborate parenting behavior. Parental care has been shown to buffer against environmental variation and alleviate or remove environmental hazards ( Smiseth et al 2012 , Grew et al 2019 ). Hence, species exhibiting parental care, such as burying beetles, are able to actively create a stable micro-environment in which offspring can thrive.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that behavioural plasticity of parental care allows parents to mitigate the impacts of environmental challenges for developing offspring in real time, and can also evolve, requires three predictions to hold at the phenotypic level. First, plastic responses by parents must exist and serve to further buffer offspring from challenging environmental conditions (Grew et al., 2019; Van Buskirk, 2012). However, increasing parental investment in response to challenging conditions is not inevitable, because doing so can elevate the costs of care and reduce lifetime fitness (Conway & Martin, 2000a; Reid et al., 2000; Williams, 1996).…”
Section: Introductionmentioning
confidence: 99%